2012
DOI: 10.1590/s1726-46342012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Maltrato infantil y del adolescente registrado en un hospital de referencia nacional, 2006 - 2011

Abstract: Objetivos. Realizar una descripción de los registros del Instituto Nacional de Salud del Niño (INSN), desde enero de 2006 hasta septiembre de 2011, sobre maltrato infantil y del adolescente, lo cual permite la caracterización del agredido y del agresor. Materiales y métodos. Se realizó un análisis de fuentes secundarias, basado en registros de la "ficha de evaluación de violencia familiar y maltrato infantil", aplicada por el Módulo de Atención al Maltrato Infantil y del Adolescente en Salud (MAMIS) del INSN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In the focus groups in stage 3, text messages about violence received high scores, which affirms the demand for information on the subject. Our results affirm the findings of past studies and reports in Peru, which have found high rates of violence in the country [ 37 – 41 ]. A study in Peru found the following for cases of sexual abuse: in 74% of cases, the perpetrators were part of the victim’s close environment; and in 38% of cases, the perpetrators were consanguineous family members [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the focus groups in stage 3, text messages about violence received high scores, which affirms the demand for information on the subject. Our results affirm the findings of past studies and reports in Peru, which have found high rates of violence in the country [ 37 – 41 ]. A study in Peru found the following for cases of sexual abuse: in 74% of cases, the perpetrators were part of the victim’s close environment; and in 38% of cases, the perpetrators were consanguineous family members [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a second effort to investigate the direction of the relationship between menarche and childhood sexual abuse, Kendall et al, interviewed 365 adults and found that the average age of onset of sexual abuse was 7 years, indicating that abuse preceded the onset of puberty [17]. A short survey of childhood abuse among children admitted to a referral hospital in Lima, Peru was able to determine that among the admitted, sexually abused girls, the average age of reported abuse was 9 years old [23]. Collectively, the US studies help to clarify the possible temporal relation between abuse experience and early menarche.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, population-based studies that have assessed racial differences in age at menarche demonstrated that non-Hispanic black women reported the earliest median age (12.1 years), non-Hispanic white women reported the latest (12.6 years) and Mexican American women fell in-between (12.3 years) [40]. Studies measuring differences in age of menarche between racial/ethnic groups are limited and few explore childhood abuse on menarche in developing countries with a high prevalence of childhood abuse, such as Peru [2123], in part due to the lack of consensus on how to define harsh physical discipline that is widespread and culturally acceptable [22]. This study is the first, to our knowledge, to examine the relationship between childhood physical and sexual abuse and age at menarche among a Peruvian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The high burden of childhood abuse in Peru and other low and middle income countries makes studying the long-term health consequences of childhood adversity a highly important global public health priority. [22] Further research is required to better understand factors that buffer or mitigate lasting health effects of early life adversity, including childhood abuse, on adult-onset asthma and other chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Peru is an example of a low and middle income country that experiences a high prevalence of childhood abuse, including both physical and sexual abuse. [22] Abuse is a perpetual cycle because victims of childhood abuse have been found to have a greater likelihood of re-experiencing adulthood abuse. [23] Prior studies have found that childhood abuse among pregnant women in Peru is associated with poor perinatal and mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%